Marine Pollution Risk Management in Marine Resources Governance and Implications for the Blue Economy - ., Triyani; Prakoso, Lukman Yudho; Suwarno, Panji (Journal of Ecohumanism, 2025)
This study aims to analyze marine pollution risk management within ocean resource governance and its implications for the blue economy. Using a qualitative literature review approach, this research explores various risk management strategies, including risk identification, assessment, mitigation, and monitoring, and their role in supporting the sustainability of blue economy sectors, such as fisheries, marine tourism, and renewable marine energy. The findings indicate that effective marine pollution risk management reduces negative impacts on marine ecosystems, enhances the quality of marine resources, and supports sustainable economic growth. However, challenges such as limited resources, lack of stakeholder coordination, and weak law enforcement hinder optimal risk management implementation. This study recommends strengthening policies, utilizing advanced monitoring technologies, and increasing public awareness to support effective marine pollution control. In conclusion, implementing appropriate marine pollution risk management within ocean governance contributes to the sustainable growth of the blue economy.